2021
DOI: 10.1140/epjc/s10052-021-09148-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of muon-induced background in MMC detector arrays for the ECHo experiment

Abstract: For above ground particle physics experiments, cosmic muons are common source of background, not only for direct detector hits, but also for secondary radiation created in neighboring materials. The ECHo experiment has been designed for the determination of the effective electron neutrino mass by the analysis of the endpoint region of the $$^{163}\text {Ho}$$ 163 Ho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Thus, muons can deposit energy directly in the MMCs and/or can generate secondary radiation, which can interact with the detector pixels. It was shown that these types of events can either be recognized with the use of an active muon veto, by searching for coincidence among pixels events and by their pulse shape [12]. Out of 242 ± 20 measured pixel-veto coincidences, 194 ± 12 events were also coincidences among pixels, leading to an efficiency of about (80 ± 8) % of detecting muon induced events by searching for coincidence among pixels.…”
Section: Muonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, muons can deposit energy directly in the MMCs and/or can generate secondary radiation, which can interact with the detector pixels. It was shown that these types of events can either be recognized with the use of an active muon veto, by searching for coincidence among pixels events and by their pulse shape [12]. Out of 242 ± 20 measured pixel-veto coincidences, 194 ± 12 events were also coincidences among pixels, leading to an efficiency of about (80 ± 8) % of detecting muon induced events by searching for coincidence among pixels.…”
Section: Muonsmentioning
confidence: 99%
“…The pulse shape analysis is based on the analysis developed to recognize muon induced events [12,38] and modified to select 163 Ho-like events. Five parameters are obtained from each pulse, its integral, rise time and amplitude on the one hand, and on the other hand, the pulse is compared to a template and is correlated with the same template.…”
Section: Upper Limitsmentioning
confidence: 99%
“…Monte Carlos simulations are used in order to understand the radiation emitting contaminants in the used material, as well as to understand the effects of cosmogenic muon generated events in the region of interest (ROI). This information, combined with the material screening, is then used to obtain a background model that is then used in the analysis of the background spectrum [11].…”
Section: Background Suppressionmentioning
confidence: 99%
“…Along this line, a search for coincident events among different detector channels allows to identify events part of these muon related events. A study of the spectrum of muons and muon-related events in the region of interest is discussed in [13].…”
Section: External Spurious Signalsmentioning
confidence: 99%
“…the fraction of muon-induced signals that produce a signal in at least two pixels. In [13], a measurement with muon veto was described for 64 pixel-days. A total of 242 ± 20 pixel-veto coincidences and 194 ± 12 pixelpixel-veto coincidences were measured.…”
Section: Background Rejection Efficiencymentioning
confidence: 99%